Facile synthesis of hierarchical nanocomposites of aligned polyaniline nanorods on reduced graphene oxide nanosheets for microwave absorbing materials. Issue 85 (24th November 2017) - Zhang, Yuefang; Liu, Jia; Zhang, Yahong; Liu, Jin; Duan, Yuping
Abstract : Hierarchical nanocomposites of aligned polyaniline nanorods on reduced graphene oxide nanosheets are synthesized in an in situ polymerization process. Abstract : A facile in situ polymerization process was introduced for the preparation of RGO–PANI hybrids with investigation of their microwave absorbing properties. The structural and morphological characterization were performed using Fourier transform infrared (FTIR), X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The results indicated that the hierarchical nanocomposites of aligned polyaniline nanorods grown vertically on the surface of RGO were successfully synthesized. The hybrids with special structure possessed more distinct dielectric response characteristics and better electromagnetic absorption properties than pure PANI. The maximum reflection loss value of the composites is up to −43 dB at 12.4 GHz and the absorption bandwidth exceeding −10 dB is 3.5 GHz with a thickness of 2 mm. The results indicate that hierarchical nanocomposites of aligned polyaniline nanorods on reduced graphene oxide nanosheets are efficient materials for microwave absorption.